Sustainable Governance in a Postsecular Public Sphere: Re‐assessing the Role of Religion as a Cosmopolitan Policy Actor in a Diverse and Globalized Age. (May 2016) - Baker, Chris
Abstract: This article nuances debates about the role and contribution of religion to sustainable forms of governance in respect of current policy and political debates. It lays out some of the definitional terms of reference around governance and sustainable development. It then locates these debates within a series of wider, interdisciplinary frameworks (primarily political philosophy, sociology, political geography and public theology), including concepts such as cosmopolitanism, the postsecular, progressive localism and spiritual and social capital. These concepts recognize the changing boundaries between the religious and secular in the public sphere. The article locates some of these theoretical discourses within two case studies of performative cosmopolitan religious governance and analyses their methodology and impact within the terms of governance and sustainable development. It concludes that performative spaces of religiously framed welfare provision and civic engagement potentially offer important pointers as to principles and structures of what sustainable governance looks like in complex, diverse and increasingly fragmented polities and localities. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment